Investigating the relationship between reward sensitivity, impulsivity, and food addiction: A systematic review - Maxwell, Aimee L.; Gardiner, Elliroma; Loxton, Natalie J. (European eating disorders review, 2020)
Objective The aim of the current research was to identify the extent to which reward sensitivity and impulsivity were related to food addiction. Method Forty‐five studies, published from 2009 to June 2019, investigating reward sensitivity and/or impulsivity with food addiction as measured by the Yale Food Addiction Scale were reviewed. Results Reward sensitivity, as measured by the Sensitivity to Reward (SR) scale, was positively associated with food addiction in two studies, but failed to yield consistent results in other studies when measured with the Behavioral Inhibition/Behavioral Activation Scales. Self‐report impulsivity, as measured by the Barratt Impulsiveness Scale (BIS‐11), was consistently associated with food addiction, with attentional impulsivity and motor impulsivity the most consistent subscales. Similarly, food addiction was also consistently associated with Negative Urgency, Positive Urgency, and Lack of Perseverance as measured by the UPPS‐P Impulsive Behavior Scale. Food addiction was inconsistently associated with disinhibition, as measured by behavioral tasks, indicating food addiction appears more aligned with self‐report measures of impulsivity. Conclusions Research in this field is dominated by university student, overweight and obese samples. Additional research is required to further tease out these relationships.